The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpubh.2021.617311
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Hot Spots, and Sociodemographic Risk Factors of Alcohol Consumption in Indian Men and Women: Analysis of National Family Health Survey-4 (2015-16), a Nationally Representative Cross-Sectional Study

Abstract: Objectives: To map the alcohol hot spots and understand the Sociodemographic Indices (SDI) affecting alcohol consumption in Indian men and women.Methods: Data from National Family Health Survey-4 carried out from 2015 to 2016 with a sample size of 103,411 men and 699,686 women were used for Geographic Information System mapping, and hot spot identification by spatial statistics (Getis-Ord Gi*). Bivariate analyses and multiple logistic regressions were used to analyze SDI.Results: India has three major alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In India, alcohol consumption is predominantly seen in males (male to female ratio of 24.3:1). 14 The suggestive evidence of alcohol abuse as the commonest aetiological factor of AP combined with the male predominance of alcohol consumption in India explains the male to female preponderance (3.5:1) in this study. Similar evidence was suggested by Dugernier T L et al 15 and Balthazar EJ et al 16 On the contrary, Raghuwanshi S et al 17 suggested the evidence of most common aetiology for AP as cholecystolithiasis (42%) followed by alcoholism (38%) with remaining 20% aetiology for AP belonged to rest category which included idiopathic, trauma and drug induced cases (24%, 2% and 2% respectively).…”
Section: Discussionsupporting
confidence: 53%
“…In India, alcohol consumption is predominantly seen in males (male to female ratio of 24.3:1). 14 The suggestive evidence of alcohol abuse as the commonest aetiological factor of AP combined with the male predominance of alcohol consumption in India explains the male to female preponderance (3.5:1) in this study. Similar evidence was suggested by Dugernier T L et al 15 and Balthazar EJ et al 16 On the contrary, Raghuwanshi S et al 17 suggested the evidence of most common aetiology for AP as cholecystolithiasis (42%) followed by alcoholism (38%) with remaining 20% aetiology for AP belonged to rest category which included idiopathic, trauma and drug induced cases (24%, 2% and 2% respectively).…”
Section: Discussionsupporting
confidence: 53%
“…Thereby, a child at the very early stage starts imitating in the same way not only in private but also in public spaces like buses, malls, streets, and more (Bhattacharyya, 2015;Bhattacharyya, 2016). There are some similar arguments that are given by Pulla (2020) 7 in his certain lectures on theories of 1…”
Section: Review Of Literature: Overview Of Domestic Violence Amidst C...mentioning
confidence: 54%
“…This variability across different states can also be due to state-wise differences in manufacturing, and sales regulations. Very high prevalence of alcohol consumption among women in Mizoram and Manipur could be attributed to lifting on ban on liquor nearly after two decades, with increasing accessibility and social acceptability of its use [ 14 , 15 ]. Also, reason behind lifting of this ban on liquor prohibition was said to be due to incidences of adverse health events due to illicit liquor consumption.…”
Section: Discussionmentioning
confidence: 99%